Novel inhibitory activity for serine protease inhibitor Kazal type-3 (Spink3) on human recombinant kallikreins - Assis, Diego Magno (2013)
Kallikrein-related peptidases (KLKs) are trypsin-like and chymotrypsin-like serine proteases which are expressed in several tissues. Their activity is tightly controlled by inhibitors including members of the serine protease Kazal-type (SPINK) family. These enzymes are promising targets for the treatment of skin desquamation, inflammation and cancer. Spink3 or caltrin I is expressed in mouse pancreas and males accessory glands and the resulting mature protein has been associated with different activities such as an inhibitor of trypsin and acrosin activity, calcium transport inhibitor in sperm and inhibitor of cell proliferation during embryogenesis. In this study, we produced a soluble recombinant Spink3 from mouse seminal vesicle (rmSpink3) that inhibited the activity of human KLKs. Using FRET substrates, rmSpink3 exhibited a potent inhibitory activity against human KLK2, KLK3, KLK5 (Ki ranging from 260 to 1500 nM), and to a lesser extent against KLK6, KLK1 and KLK7 (Ki around 3000 nM). As shown by mass spectrometry analysis of rmSpink3 incubated with trypsin, the inhibitor was not truncated by the target enzyme. Based on the in silico analysis of the expression of Spink3/SPINK1 and KLKs it is speculated that some KLKs may be natural targets of Spink3/SPINK1, however experimental confirmation using both proteins from mouse or human origin is needed. This work shows that rmSpink3 is a potent inhibitor of various human KLK members suggesting the potential of this molecule in the diagnosis/prevention of several human diseases.